The Reconfiguration of Local Government Oversight Powers Regarding Environmental Crimes Following The Amendment of The Mining Law: A Legal-Political Analysis of Development From A Historical Perspective (1967–2025) - Dedi Iskandar Batubara; Muhammad Khutub (Lembaga Bale Literasi, 2025)
This study aims to analyse the reconfiguration of supervisory authority over environmental crimes in the mining sector, particularly regarding the role of local governments following the amendment of the Mineral and Coal Law from a developmental legal-political perspective. This study employs a normative legal method using legislative, historical, and conceptual approaches. The scope of the study covers four main legal regimes, namely Law No. 11 of 1967, Law No. 4 of 2009, Law No. 3 of 2020, and Law No. 2 of 2025. The research findings indicate that supervisory authority has undergone a cyclical paradigm shift, moving from centralisation towards decentralisation, and then back to re-centralisation with a strategic orientation based on national interests and the agenda for sustainable economic development. From the perspective of development legal politics, these changes reflect the state’s dominance in controlling strategic resource sectors to support economic growth, industrial downstreaming, and the enhancement of national competitiveness. However, the re- centralisation of authority implies a weakening of the role of local governments in operational supervision at the local level, thereby creating a gap between regulatory design and implementation on the ground. This situation contributes to an increased risk of environmental crimes, such as illegal mining, pollution, and ecosystem degradation with far-reaching impacts. Therefore, this study proposes a Hybrid Developmental Supervision model that integrates the role of the central government as a strategic regulator, local governments as operational supervisors, and the public as participatory supervisors. This model is expected to enhance the effectiveness of supervision and realise sustainable, adaptive, and equitable environmental governance.